Wind ENERGY in Russia: The current state and development trends - Artem Kudelin; Vladimir Kutcherov (Energy Strategy Reviews, 2021)
Abstracts: Wind energy is one of the leading forms of non-hydro renewable energy sources in the world. Russia ranks among the top countries with vast wind energy resources and among the top CO2 producers as well. Simultaneously, the utilization of wind energy is extremely low compared to other CO2 emitting states. This paper aims to describe the ongoing situation for wind energy development according to the most critical aspects that affect evolution. Investor support schemes, permission procedures, social, educational, and research issues, available data on wind energy resources and local production facilities, and supportive policies are also described. A discussion on possible obstacles and limits to windfarm deployment and probable capacity growth scenarios has been provided. Trends for different economic development prognoses were evaluated considering possible outcomes for wind energy facilities introduction. The optimistic scenario suggests that, depending on global economic growth by 2030, the volume of wind generation capacity could reach up to 10 GW by 2030. The pessimistic scenarios, more probable due to the COVID-19 pandemic, limit the growth by 3.6 and 6.4 GW depending on the gross domestic product volumes decrease. The threats to the renewable energy sources development in Russia due to the world's current situation are summarized in conclusion.